Effect of temperature on spiking patterns of neocortical layer 2/3 and layer 6 pyramidal neurons - Waters, Jack; Hedrick, Tristan (Frontiers in Neural Circuits, 2012)
The spiking patterns of neocortical pyramidal neurons are shaped by the conductances in their apical dendrites. We have previously shown that the spiking patterns of layer 5 pyramidal neurons change with temperature, probably because temperature modulates the electrical coupling between somatic and dendritic compartments. Here we determine whether temperature has similar effects on the spiking patterns of layer 2/3 and layer 6 pyramidal neurons in acute slices of mouse primary motor cortex. In both cell types, decreasing temperature led to more irregular spiking patterns. Our results indicate that a decrease in spiking regularity with decreasing temperature, probably mediated by increased electrical coupling between soma and dendrites, is common to all pyramidal neurons in motor cortex.